PENGARUH MOTIVASI DAN KESEJAHTERAAN TERHADAP SEMANGAT KERJA DAN IMPLIKASINYA TERHADAP KINERJA - Agustin Riyan Pratiwi; Febi Firgiyani (Perwira Journal of Economics & Business, 2021)
This research objectives to knot the effect of motivation and morale and welfare of the implications on performance. This study using path analysis (path analysis) and testing using F test and t test. Research shows that motivation in the high category, well-being of employees included in the category of very high morale of employees included in the high category and performance of employees included in the high category. Overall it can be concluded there is a motivational effect on morale, there is the effect of welfare on morale, there is the influence the morale of the performance there are significant simultaneously motivation and well-being against the spirit of the work, there is the effect of simultaneous motivation and well-being against the spirit of the work and its implications for performance.